Model of Entrepreneurship in Elementary Schools in the Era of Independent Learning in the Age of Society 5.0 - Dhiniaty Gularso (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
One of the goals of the Indonesian nation being established is to create general welfare for the people of Indonesia. The study aims at finding an appropriate entrepreneurial model in the field of basic education. This research method was a qualitative case study type. The research data was in the form of observations, interview transcripts and documentation. The research analysis used the Miles and Huberman Model which included data collection, data reduction, data presentation and drawing conclusions. The results showed that entrepreneurship in education is an effort to increase added value to a product/service in the profession that is involved in the field of education. Entrepreneurship in education is entrepreneurship that is relevant or in-line with the profession they are engaged in in the world of education so that professionalism is maintained and does not harm other parties in it. Principals, teachers, education staff can develop an entrepreneurial spirit by making education units. Its goal is to become a school that provides student learning experiences according to students' interests and talents according to the concept of independent learning and collaborated with technology and according to the demands of the current era in accordance with the demands of Society 5.0.